(3GdYOO GdeYOhO aj GdeMGVQGJs - (3RcQjG Hf YHO Gddg GdeQGZj, CHh jMji,J (B550 (3g` s ((3Uaj GdOjf Hf eMeO Hf MSf Hf Ydj Hf eMeO Hf CMeO GdNdjdj GdeNRhej s)
(3ChdgG (B:s
(3GdKGef(B: (3GdeOM bGd GdfHj (B((3U(B): (3YLHJ ef TGFH djS dg UHhI s
(3BNQgG (B:s
(3GdeSHY(B: (3bGd GdfHj (B((3U(B) (3eG jfJXQ CMOce ef GdOfjG EdG Zfi eWZjkG, Ch abQkG efSjkG, Ch eQVG eaSOkG, Ch gQekG eYJdG, Ch ehJG s
(3HChdgG JedjcGJ efgG ddYGde GHf CHj GdSQhQ GdHcQj GdUOjbj eDQN SfI (B1032(3g`s
(3hHgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3gh faS fSNI GdLRA GdChd GdSGHb GdeQbe (B1815 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B182s
Keywords: (3GdCOHs